STRUKTUR PENYAJIAN TARI LADUN DALAM SENI MENDU PENGGAL RAJA MUDA KABUPATEN NATUNA PROVINSI KEPRI - Timia, Timia; Ismunandar, Ismunandar; Istiandini, Winda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The purpose of this research was to describe the structure of the dance presentation which has its own characteristics, in terms of motion, music, costumes, and lyrics of songs contained in Ladun dance music, the art of Mendu Penggal Raja Muda, Natuna Regency, Riau Islands Province. The method used in this research was descriptive method in the form of qualitative. The approach used by researchers was a choreography approach. To complement the research data, researchers used observation, interviews, and documentation. Techniques to test the validity of data was source triangulation. Researcher used data reduction, data presentation, as well as inference and verification as the data analysis techniques. The result of the research is the analysis of the main elements of the structure, top design, floor design, music accompaniment and the Islamic nuance which full of advice and prayer. The theme is related to life events in the kingdom. The dressing used is the character of a firm person of Antapura kingdom. Ladun dance is performed at the inauguration ceremony and marriage. The dance serves as an entertainment. The results of this research is expected to be implemented in the arts and culture grade X, semester I in high school, so that students better understand the existence of traditional dance in Natuna Regency, Riau Islands Province. Keywords: presentation structure, Ladun dance, the art of Mendu Penggal Raja Muda.